Assessment of students' knowledge of cardiopulmonary resuscitation - Pierzak, Monika Teresa; Nowak, Ewelina (Journal of Education, Health and Sport, 2018)
Summary Introduction. First aid is a legal and moral obligation of every citizen. However, quite a widespread lack of knowledge, even among people completed the training, reduces the victim's chance of survival in an emergency. Just a quick response and properly given first aid at the scene witness decides about the experience of others. Objective: The aim of the study was to assess the knowledge of students of medical and non-medical in the field of cardiopulmonary resuscitation. Material and methods: The study included 137 students of two universities in Kielce, including 77 medical students and 60 non-medical students. In this study method was used diagnostic survey, based on an anonymous questionnaire by their own. Results. Of the 14 questions in the field of cardiopulmonary resuscitation, there was the advantage of correct answers in medical students. Students of non-medical showed a higher knowledge only 2 questions. The low level of knowledge is concerned that the participation of more than 80% of the respondents in training on first aid. Only a total of 33 students declare that they would be able to provide first aid at the scene. Conclusions. The level of knowledge of cardiopulmonary resuscitation among students of medical and non-medical is unsatisfactory, which requires changes in education and promotion of training in this field.